2008
DOI: 10.1097/mcg.0b013e31811edcb7
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Intravenous Contrast-enhanced 16-raw Multidetector CT Colonography for Detecting Patients With Colorectal Polyps in an Asymptomatic Population in Korea

Abstract: Screening by CTC with asymptomatic population was not promising in Korea despite using advanced CT technology (16-row detector). Bowel preparation was one of the key determinants of the specificity of CTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…We included five studies with in total 4,086 patients (54% male). Four studies [2628, 30, 31] did have a study population of over 200 average risk subjects, the largest population comprised 2,249 average risk subjects [27]. The smallest study had a population of 68 participants at average risk [29].…”
Section: Resultsmentioning
confidence: 99%
“…We included five studies with in total 4,086 patients (54% male). Four studies [2628, 30, 31] did have a study population of over 200 average risk subjects, the largest population comprised 2,249 average risk subjects [27]. The smallest study had a population of 68 participants at average risk [29].…”
Section: Resultsmentioning
confidence: 99%
“…We included 47 prospective studies involving 10,546 patients that compared CTC to the reference standard of CC or surgery [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Table 2 shows detailed information from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…The trial was registered in the Dutch trial register (trial NTR1829; www .trialregister.nl). C omputed tomographic (CT) colonography is an accurate technique for the detection of advanced neoplasia (colorectal cancer and advanced adenomas), the target lesion in colorectal cancer screening (1)(2)(3)(4)(5). Revised colorectal screening guidelines recommend that screening with CT colonography be performed every 5 years, and other guidelines have indicated that CT colonography is a promising screening technique (6)(7)(8).…”
Section: Patients and Settingsmentioning
confidence: 99%